2010
DOI: 10.1029/2010jg001298
|View full text |Cite
|
Sign up to set email alerts
|

Change of microbial communities in glaciers along a transition of air masses in western China

Abstract: [1] Microbial community dynamics across glaciers in different climatic zones provide important information about the sources, transportation pathways, and deposition of microorganisms. To better understand the possible driving forces of microbial community shifts in glacier ice at a large spatial scale, 16S rRNA gene amplification was used to establish clone libraries containing 95 bacterial sequences from three different habitats in the Qiangyong Gacier in 2005. The libraries were used in phylogenetic compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Members of the genus Corynebacterium were detected in the permafrost and Antarctic soils (Cherbunina et al, 2011;Horowitz et al, 1972). Genera which were detected in significant amounts in both DNA and cDNA libraries (Aquabacterium, Aquaspirillum, Comamonas, Janthinobacterium, Acinetobacter) were also detected previously (as evidenced by rDNA library analyses) in cold different environments, such as Tibetan glaciers and coastal Antarctic waters Bej and Mojib, 2009;Garrison et al, 1986;Gentile et al, 2006;Junge et al, 2004;Liu et al, 2006;Segawa et al, 2005;Xiang et al, 2010). Some of the genera, which we found only in DNA libraries, have been previously detected in cold environments.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Members of the genus Corynebacterium were detected in the permafrost and Antarctic soils (Cherbunina et al, 2011;Horowitz et al, 1972). Genera which were detected in significant amounts in both DNA and cDNA libraries (Aquabacterium, Aquaspirillum, Comamonas, Janthinobacterium, Acinetobacter) were also detected previously (as evidenced by rDNA library analyses) in cold different environments, such as Tibetan glaciers and coastal Antarctic waters Bej and Mojib, 2009;Garrison et al, 1986;Gentile et al, 2006;Junge et al, 2004;Liu et al, 2006;Segawa et al, 2005;Xiang et al, 2010). Some of the genera, which we found only in DNA libraries, have been previously detected in cold environments.…”
Section: Discussionmentioning
confidence: 68%
“…Variovorax paradoxus grows at low temperatures and is likely an indigenous member of snow microbiota (Segawa et al, 2005). Sphingomonas, Pseudomonas, Methylobacterium, Flavisolibacter, and Stenotrophomonas were found multiple times in snow and glaciers in Tibet Christner et al, 2002;Liu et al, 2006;Miteva, 2008;Segawa et al, 2005;Xiang et al, 2010). Members of the genus Corynebacterium were detected in the permafrost and Antarctic soils (Cherbunina et al, 2011;Horowitz et al, 1972).…”
Section: Discussionmentioning
confidence: 96%
“…Bacteria are the most dominant life forms in extremely cold, oligotrophic, and frozen water environments. Some of the glacier bacteria have been found to be phylogenetically distinct from those found in temperate environments, demonstrating the biogeography of individual microorganisms in the glacier ice (Christner et al, 2003; Xiang et al, 2010; Anesio and Laybourn-Parry, 2012; Franzetti et al, 2013; Knowlton et al, 2013). Previous studies have also shown apparent geographic patterns of microbial communities across the snow slope surfaces of mountain glaciers Kuytun 51, Qiangyong, and Rongbuk and among the mountain ice cores Dunde (140-m-long, drilled in 1987), Malan (102-m-long, drilled in 1999), Muztagata (37-m-long, drilled in 2003), and Puruogangri (89-m-long, drilled in 2000), and deep ice cores Greenland GISP2D and Antarctic Vostok 5G and Byrd, which illustrates the various microbial responses to climatic and environmental changes of glaciers and ice sheets (Xiang et al, 2009, 2010; An et al, 2010; Knowlton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few taxonomic groups are able to colonize and dominate in the snow, although numerous microorganisms are trapped in the surface snow (Zhang et al, 2008, 2009; Xiang et al, 2009, 2010; An et al, 2010). Previous limited data of glacier surface snow have shown that the bacteria Comamonadaceae and Flavisolibacter sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation